NOTION OF INTANGIBLE INHERITANCE IN IBN ’ARABI - Singh, David Emmanuel (Journal of Dharma, 1999)
Affifi has noted three ways to knowledge in Ibn ’Arabi’: (i) Reason, (ii) Prophets’: example and the Scriptures, (iii) Spiritual experience’. He has shown that’ according to Ibn ’Arabi, the philosophers’ reason and blind following of the example of the prophets and the scriptures may lead to some truth, but a complete awareness of the way of the prophet becomes possible only through direct experience. The following discussion seeks to make a brief exploration of the